Perception, politics, and security in South Asia : the compound crisis of 1990 - Chari, P. R. (RoutledgeCurzon advances in South Asian studies, 2003)
This book provides a detailed examination of the compound crisis between India and Pakistan that brought the region to the brink of a nuclear war in 1990 and places the crisis in the context of concurrent international events.